Changes in soil moisture predict soil carbon losses upon rewetting in a perennial semiarid steppe in SE Spain - Rey, Ana Lía (2017)
Our understanding of the spatial and temporal dynamics of soil CO2 pulses after rainfall events is still limited and thus, our capacity to predict the consequences of future changes in precipitation patterns for dryland soils. In this study we examined the response of soil CO2 pulses to rainfall size and pre-rain soil moisture conditions in a semiarid grassland. In a first experiment, we manipulated the amount of rainfall in a factorial combination that included three levels of rainfall size (1, 5 and 15 mm), three soil covers: vegetated areas (VEG), biological soil crusts (BSC) and bare soil (BS) and two nearby sites: a natural grassland and a degraded grassland. We measured soil CO2 efflux over 24 h to capture rainfall pulses. In a second experiment conducted at the natural grassland, we measured soil CO2 efflux after manipulating soil moisture to its full range in the area by wetting the soil to: 0–10%, 10–15%, 20–25%, 30–35% water content levels. All soil covers responded to the rainfall treatments within minutes, reaching up to 120 times baseline values and shortly returning to background rates. Rainfall size had a larger impact on the response than pre-rain soil moisture conditions. Whereas in most cases rainfall amount increased soil CO2 pulses, initial moisture conditions did not affect total carbon losses despite much larger CO2 peaks in very dry soils. Interestingly, even extremely low rainfall events (1 mm) caused significant carbon losses. The amount of carbon lost after rainfall events ranged from 0.45 in bare soils to 1.18 g C m− 2 day− 1 in vegetated areas. Overall, rainfall had a larger impact in vegetated areas at the degraded site implying that larger carbon losses can be expected as a result of land degradation. Sudden changes in soil moisture caused by rainfall predicted 65% of total carbon losses in BS, 70% in BSC and 80% in VEG at both sites. However, the slope was significantly lower in bare soils suggesting substrate limitation. Since most of the carbon resides belowground in these grasslands, carbon losses as a result of larger rainfall events and longer dry periods in this area could have important consequences for soil carbon stocks.